URGENSI PENGAJARAN ISLAM NUSANTARA PADA PROGRAM STUDI VOKASIONAL DI PERGURUAN TINGGI DALAM MENANGKAL RADIKALISME - Muhammad Asrori (Universitas Islam Lamongan, 2017)
Islam Nusantara (Islam of the archipelago) is a new term having recently captivated especially Muslim scholars. Islam Nusantara is the discourse about Islam as a religion having an encounter with tradition in the archipelago. Such encounter has resulted in a distinctive religious tradition which is considerably different from that of other regions. While radicalism in Islam is a form of in-depth (radic) understanding in Islam. Instead of having the in-depth understanding of Islam, radical Islam is a form of Islamic understanding that tends to be